MODEL MENTAL SISWA SMA DALAM MEMAHAMI KONSEP LARUTAN ELEKTROLIT DAN NON-ELEKTROLIT - Suliyana Ibrahim; Mangara Sihaloho; Masrid Pikoli (Lantanida Journal, 2022)
This objective of this study for investigate mental models of SMA Negeri 1 Telaga students about electrolyte and non-electrolyte solutions. Data was collected by giving a mental model test in the form of two-level multiple choice in class X involving 196 students. The results showed that the analysis of the mental model of students of class X science about electrolyte and non-electrolyte solutions was 38% classified as scientific mental models and 62% alternative mental models, which consisted of 30% partially correct mental models, 32% misconceptions (Specific Misconception) and 0% no response (No Responds). Thus, most students do not yet have a complete mental model in understanding the material of electrolyte and non-electrolyte solutions.